Các yếu tố tác động đến việc tham gia VietGap của hộ trồng thanh long: Nghiên cứutại huyện Hàm Thuận Bắc, tỉnh Bình Thuận - Nguyen Minh, Ha; Nguyen Van, Hung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
The purpose of this study is to analyze the factors influencing the adoption of VietGAP of dragon fruit growers and thus to propose several implications for the development of dragon fruit cultivation. By using Logit regression technique and a sample of 273 farm households in Ham Thuan Bac District, Binh Thuan Province in 2014, its results indicate that many variables affecting VietGAP adoption comprise those involving househoulder’s/household’s characteristics, those relating to household income, those denoting household’s expectations for VietGAP, and those directly concerning state support and VietGAP information.